Wood Nutrient-Water-Density Linkages Are Influenced by Both Species and Environment - Demetrius Lira-Martins; Demetrius Lira-Martins; Carlos Alberto Quesada; Stanislav Strekopytov; Stanislav Strekopytov; Emma Humphreys-Williams; Bruno Herault; Bruno Herault; Bruno Herault; Jon Lloyd; Jon Lloyd; Jon Lloyd (Frontiers in Plant Science, 2022)
Tropical trees store a large amount of nutrients in their woody tissues, thus triggering the question of what the functional association of these elements with other wood traits is. Given the osmotic activity of mineral elements such as potassium, sodium, and calcium, these elements should be strong candidates in mediating the water storing capacity in tropical trees. We investigated the role of wood nutrients in facilitating wood water storage in trees by using branch samples from 48 tropical tree species in South America and examined their associations with wood density (ρ). Wood density varied from 316 kg/m3 in Peru plots, where the soil nutrient status is relatively higher, to 908 kg/m3 in Brazil plots, where the nutrient availability is lower. Phosphorus content in wood varied significantly between plots with lowest values found in French Guiana (1.2 mol/m3) and plots with highest values found in Peru (43.6 mol/m3). Conversely, potassium in woody tissues showed a significant cross-species variation with Minquartia guianensis in Brazil showing the lowest values (8.8 mol/m3) and with Neea divaricata in Peru having the highest values (114 mol/m3). We found that lower wood density trees store more water in their woody tissues with cations, especially potassium, having a positive association with water storage. Specific relationships between wood cation concentrations and stem water storage potential nevertheless depend on both species’ identity and growing location. Tropical trees with increased water storage capacity show lower wood density and have an increased reliance on cations to regulate this reservoir. Our study highlights that cations play a more important role in tropical tree water relations than has previously been thought, with potassium being particularly important.